Analysis of DKI Jakarta's APBD Fund Allocation Policy for Improving the Quality of Public Services at the City Level - Rahmin W, Wa Ode; Ahmad, Badu; Rusdi, Muhammad (IHSA Institute, 2024)
This study aims to analyze the effectiveness of the allocation of funds from the Jakarta Regional Revenue and Expenditure Budget (APBD) in supporting the improvement of the quality of public services at the city level. By taking a qualitative approach, data was obtained from literature studies and analysis of documents related to the management of the Jakarta Regional Budget from 2008 to 2012. The results show that although there is an increase in regional revenue and expenditure growth during this period, there are still obstacles that hinder the effectiveness of APBD fund allocation, such as budget irregularities, weak budgeting control, and political dominance in budget decision-making. However, efforts to strengthen transparency, accountability, and community participation in the budgeting process were identified as potential solutions to address these barriers. This study illustrates the importance of effective management of public funds in improving the quality of public services at the city level, especially in the context of the Jakarta Regional Budget